Traditional and family values as the basis of gender attitudes of youth - Biserova, Galia; Ldokova, Galiya; Shagivaleeva, Guzalia (Interacción y Perspectiva, 2025)
The article analyzes how the gender approach influences the formation of traditional family values, especially in young people affected by traumatic contexts. It proposes an education that combines gender roles with cultural values, adapting to social changes. It examines regional differences in Russia and their impact on gender attitudes. It is an important task of our society, and consequently of the entire national education system, to educate children and young people in the context of inculcating traditional and family values, awareness of the mission of men and women and preparing them to carry it out. At the same time, living for long periods in combat zones and on the front line, and being in prolonged traumatic situations, makes young people in the new regions of the Russian Federation the most vulnerable to this problem. The article offers a brief theoretical perspective to understand the problem of family and marriage values and traditions in modern society. It examines the traditional and family values of boys and girls in the historical and new regions of Russia and their influence on the formation of gender attitudes, according to cultural ideas about the role, position and purpose of men and women in society. Therefore, the gender approach allows considering the sociobiological characteristics of gender, the assimilation of norms of behavior and activity in society, as well as the interests, needs, and preferences inherent to a specific gender role.